ASNB Teluk Intan / Nur Afza Afrina Ahmad Azizi - Ahmad Azizi, Nur Afza Afrina (Universiti Teknologi MARA, Perlis, 2023)
Internships are short-term work experiences provided by a company or organization to commonly final-year students for them to gain real-world work experience and gain exposure to the industry relevant to their course. Most fresh graduates have a grape between their university life and their working life, so the purpose of the industrial training is to help all students out there an experience and an exposure on what the real working life is like. I have been experienced industrial training for almost 6 months starting from 29th August 2022 and ended on 10th February 2023. I was accepted to undergo my industrial training at Amanah Saham Nasional Berhad (ASNB) branch Teluk Intan. I was placed at the Customer and Channel Management Department under Branch Management & Supervision Unit of ASNB Teluk Intan. As an intern at ASNB Teluk Intan, I have gained a real working experience, understanding more about the company operating structure and the company’s products. Throughout my internship at ASNB Teluk Intan it helps me to enhanced my communication skills and makes me become braver because I have been dealing with customers a lot. Starting this report with my updated resume, which I will be using to search for any available opportunities. After that, I will be explained about company’s profile including company’s background, vision and mission, company’s product, its location, and company’s organizational structures. Besides, I will be sharing about the training reflection during my internship at ASNB Teluk Intan. The most important aspect of this report is that I will present a SWOT analysis for the company, along with discussions and recommendations. Lastly, I will be concluded overall regarding my industrial training at ASNB Teluk Intan.